Technological Innovation in International Training and Advancing Health Services: Two Cases During the COVID-19 Pandemic - Caroline Benski; Aya Goto; Abéline Hantavololona; Vonimboahangy Andrianarisoa; Paulin Ramasy Manjary; Giovanna Stancanelli; Saekhol Bakri; Muflihatul Muniroh; Chihaya Koriyama (Taylor & Francis Group, 2024)
Beginning in 2020, the COVID-19 pandemic limited onsite international activities and challenged us to plan and implement new ways of collaboration. We reviewed our online trials during a three-year period to better understand how to use digital technologies to continue knowledge and skills transfer. In this cross-national case study, we compare two illustrative cases: Japanese experts training Indonesian health professionals for participatory school health education, and Swiss experts training Malagasy health providers for respectful obstetric and newborn emergencies. We first describe our cases, referring to Vargo's framework for summarizing reports on digital technology usage. Second, we draw commonalities between the two cases. Third, gleaned from these experiences during the pandemic, we offer a practical framework for efficient and effective international collaboration using new technologies. For both cases, basic digital technologies, such as online meetings and e-mailing, were used and training sessions were successfully conducted. Trusting relationships between the training and participant groups were in place before the pandemic. This led to enthusiasm for continuing learning even after the pandemic started. Our case comparison presents the usefulness of digital technologies for continuing international collaboration and highlights the importance of human factors, such as trusting relationships and enthusiasm to pursue a shared goal, as the basic condition for success.